2017
DOI: 10.4049/jimmunol.1601415
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of B Cell Repertoire Formation in Myasthenia Gravis Patients Revealed through Deep Sequencing

Abstract: Myasthenia gravis (MG) is a prototypical B cell-mediated autoimmune disease affecting 20–50 per 100,000 people. The majority of patients fall into two clinically distinguishable types based on whether they produce autoantibodies targeting the acetylcholine receptor (AChR-MG) or muscle specific kinase (MuSK-MG). The autoantibodies are pathogenic, but whether their generation is associated with broader defects in the B cell repertoire is unknown. To address this question, we performed deep sequencing of the B ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
103
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 96 publications
(114 citation statements)
references
References 77 publications
2
103
1
2
Order By: Relevance
“…The most prominent repertoire abnormality involved the biased use of variable (V) region gene segments. We observed significant shifts in the relative abundance and variability of each V gene family between MuSK MG and HDs . In the naive compartment of MuSK MG subjects, V‐family biases were observed in the form of decreased usage of IGHV3 as well as an increase in IGHV1 and IGHV4 usage.…”
Section: The Circulating B Cell Repertoire In Musk Mg Is Distortedmentioning
confidence: 86%
See 1 more Smart Citation
“…The most prominent repertoire abnormality involved the biased use of variable (V) region gene segments. We observed significant shifts in the relative abundance and variability of each V gene family between MuSK MG and HDs . In the naive compartment of MuSK MG subjects, V‐family biases were observed in the form of decreased usage of IGHV3 as well as an increase in IGHV1 and IGHV4 usage.…”
Section: The Circulating B Cell Repertoire In Musk Mg Is Distortedmentioning
confidence: 86%
“…We recently applied this approach to compare the broad repertoire features of both the naive and memory B cell compartments in MuSK MG patients with those of healthy donors (HDs) . We reasoned that a disease driven by autoantibodies may have conspicuous abnormalities present in the circulating B cell repertoire.…”
Section: The Circulating B Cell Repertoire In Musk Mg Is Distortedmentioning
confidence: 99%
“…82 In contrast, naive BCR repertoires from MG patients were highly diverse among individuals and may reflect dysregulated B-cell development in these patients. 81 ities. An AIRR-seq investigation revealed that differential expression of IGHV genes in the repertoires from SSc cohorts relative to a healthy cohort are present in the IgD/IgM compartment.…”
Section: Toler An Ce Check P Oint Defec Ts Alter the Naive B-cell Rmentioning
confidence: 99%
“…80 We more specifically applied AIRR-seq to analyze the BCR repertoire of naive B cells from AChR and MuSK MG patients that are enriched in autoreactive clones due to impaired central and peripheral B-cell tolerance checkpoints in MG and compared them to those of healthy donors (HD) to potentially identify naive BCR repertoire features associated with autoimmunity. 81 Our initial study focused on determining whether the naive BCR repertoires in MG included both skewed immunoglobulin gene usage and physiochemical properties. 81 In agreement with a previous study, the naive B-cell repertoires obtained from multiple healthy control subjects displayed highly consistent IGH variable (IGHV) gene usage with limited variability.…”
Section: Toler An Ce Check P Oint Defec Ts Alter the Naive B-cell Rmentioning
confidence: 99%
“…Although broad immune dysregulation (13)(14)(15) in MuSK MG is recognized, the mechanistic details of autoantibody production remain undefined. Given that MuSK MG autoantibodies are required for pathogenesis (2) and that they are, consequently, the fundamental target of immunotherapy, it is important to establish how they are generated.…”
Section: Introductionmentioning
confidence: 99%